Species and Genotypic Diversities and Similarities of Pathogenic Yeasts Colonizing Women - Xu, Jianping (American Society for Microbiology, 1999)
We examined the patterns of strain relatedness among pathogenic yeasts from within and among groups of women to determine whether there were significant associations between genotype and host condition or body site. A total of 80 yeast strains were isolated, identified, and genotyped from 49 female volunteers, who were placed in three groups: (i) 19 women with AIDS, (ii) 11 pregnant women without human immunodeficiency virus (HIV) infection, and (iii) 19 women who were neither pregnant nor infected with HIV. Seven yeast species were recovered, including 59 isolates of Candida albicans, 9 isolates of Candida parapsilosis, 5 isolates of Candida krusei, 3 isolates of Candida glabrata, 2 isolates of Saccharomyces cerevisiae, and 1 isolate each of Candida tropicalis and Candida lusitaniae. Seventy unique genotypes were identified by PCR fingerprinting with the M13 core sequence and by random amplified polymorphic DNA analysis. Of the nine shared genotypes, isolates from three different hosts were of one genotype and pairs of strains from different body sites of the same host shared each of the other eight genotypes. Genetic similarities among groups of strains were calculated and compared. We found no significant difference in the patterns of relatedness of strains from the three body sites (oral cavity, vagina, and rectum), regardless of host conditions. The yeast microflora of all three host groups had similar species and genotypic diversities. Furthermore, a single host can be colonized with multiple species or multiple genotypes of the same species at the same or different body sites, indicating dynamic processes of yeast colonization on women.